Everyday Knowledge, Education and Sustainable Futures Transdisciplinary Approaches in the Asia-Pacific Region - Robertson, Margaret; Tsang, Po Keung Eric (Education in the Asia-Pacific Region: Issues, Concerns and Prospects,, 2016)
Everyday knowledge offers opportunities for better understanding of significant issues of our times. Reflecting these themes this book places emphasis on community wisdom. The underpinning argument is that our instinctive urge for survival may not be enough if we do not share our collective knowledge and learn more about the everyday habits, beliefs and actions of communities spread across the region. Contributions from researchers active within local communities help build knowledge capacity and support for collaborative research.